How to normalize monetary policy in the Euro area - Guenter W. Beck; Volker Wieland (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2017)
Since 2014 the ECB has implemented a massive expansion of monetary policy including large-scale asset purchases and negative policy rates. As the euro area economy has improved and inflation has risen, questions concerning the future normalization of monetary policy are starting to dominate the public debate. The study argues that the ECB should develop a strategy for policy normalization and communicate it very soon to prepare the ground for subsequent steps towards tightening. It provides analysis and makes proposals concerning key aspects of this strategy. The aim is to facilitate the emergence of expectations among market participants that are consistent with a smooth process of policy normalization.
urn:nbn:de:hebis:30:3-438808
Keywords: 330